PERAN DATA SPASIAL DALAM INTEGRASI KEARIFAN LOKAL TETEU AMUSIAT LOGA SEBAGAI MITIGASI BENCANA TSUNAMI PADA MASYARAKAT PULAU SIBERUT - Jefri Nando; Risky Ramadhan (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Siberut Island is one of the areas prone to earthquake and tsunami disasters in West Sumatra. This area has a high accumulation of stress, which has the potential to cause large earthquakes and tsunamis. To reduce this risk, disaster mitigation is needed and in this case the Mentawai people have local wisdom which is used as an Early Warning System. The aim of this research is to analyze the use of Geographic Information Systems (GIS) to determine the tsunami inundation hazard index in tsunami disaster mitigation efforts and to analyze the role of Teteu Amusiat Loga local wisdom as an Early Warning System. This research uses a mixed method design with a quantitative and qualitative approach that combines spatial and SWOT analysis. Descriptive analysis using the SWOT method was carried out by looking at internal and external factors in local wisdom-based disaster mitigation which were then identified with the elements of Strength, Weakness, Opportunity and Threats. From this research, it was found that the high tsunami inundation hazard area of ​​10m was 14143.81 ha, 15m total 19737.38 and 20m 25154.3 ha with a total hazard area of ​​59035.49 ha. In this case, local wisdom has an important role in disaster mitigation, one of which is through the song Teteu Amusiat Loga which is used as an Early Warning System, but there is a level of knowledge related to this song in various age groups. The research results also explain that mass media and modern communication platforms provide opportunities to develop local wisdom, but this local wisdom is not in accordance with modern standards for disaster mitigation.